1987
DOI: 10.1002/tera.1420350116
|View full text |Cite
|
Sign up to set email alerts
|

Embryotoxicity of sex steroidal hormones in nonhuman primates: II. Hydroxyprogesterone caproate, estradiol valerate

Abstract: Two sex steroid compounds which have been used clinically for parenteral supportive therapy of pregnancy were examined for embryotoxic effects in rhesus and cynomolgus macaques. Hydroxyprogesterone caproate (HPC) alone or in combination with estradiol valerate (EV) were administered intramuscularly (i.m.) to pregnant monkeys at 7-day intervals between 20 and 146 days of gestation and fetuses were examined following cesarean section at 150 +/- 2 days. HPC alone was tested in both species at doses ranging from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…17-OHPC has been reported to have a clinical signal for embryofetal toxicity in the human trials conducted to date (Christian et al, 2007), and a similar signal has been observed in rhesus monkeys (Hendrickx et al, 1987). However, in the absence of elaborate reproductive toxicology and pharmacokinetic studies in animals and humans, the data are inconclusive to address the embryo-fetal toxicity issues vis-à-vis 17-OHPC and/or its metabolites.…”
Section: Discussionmentioning
confidence: 95%
“…17-OHPC has been reported to have a clinical signal for embryofetal toxicity in the human trials conducted to date (Christian et al, 2007), and a similar signal has been observed in rhesus monkeys (Hendrickx et al, 1987). However, in the absence of elaborate reproductive toxicology and pharmacokinetic studies in animals and humans, the data are inconclusive to address the embryo-fetal toxicity issues vis-à-vis 17-OHPC and/or its metabolites.…”
Section: Discussionmentioning
confidence: 95%
“…Early mouse studies demonstrated teratogenicity of estradiol salts, including cleft palate with estradiol benzoate (64) and eyelid and mammary defects with estradiol dipropionate (65). However, studies in monkeys using estradiol salts in combination with hydroxyprogesterone caproate failed to show a relationship between estrogen and congenital anomalies (66).…”
Section: Estrogensmentioning
confidence: 97%
“…Furthermore, in a recent very large preterm birth prevention study of singleton pregnancies, no cases of miscarriage associated with the use of micronized natural progesterone were observed [102]. On the other hand, 17-OHP-C is associated with an increase in resorption (miscarriage) in pregnant rats [96], total embryo-lethality in pregnant rhesus monkeys [103], a signal for a 30% increase in miscarriage in a meta-analysis of 17-OHP-C clinical studies [81], as well as an imbalance in miscarriage associated with 17-OHP-C in the largest placebo controlled randomized trial published to date [83]. In a study by Rebarber et al [104], patients who received prophylactic treatment with 17-OHP-C had a higher incidence of gestational diabetes (odds ratio 2.9 [95% CI: 2.1-4.1]) than those who were not treated.…”
Section: Preventive Toolsmentioning
confidence: 99%